The Application and Discussion of Virtual Network Technology in Computer Network Security - Tang, Mingxing (Journal of Artificial Intelligence and Information, 2025)
The development of information technology has led to an improvement in people’s living standards and quality of life. With the widespread adoption of current computer technology, concerns about computer network security are increasingly shared among users. The application of virtual network technology in computer networks can significantly enhance network security and reduce the losses caused by computer vulnerabilities. This paper primarily investigates the utilization of virtual network technology in computer networks and presents the application scenarios of virtual network technology in computer network security. It aims to provide effective references for the application of relevant technologies.